2005
DOI: 10.1177/112070000501500305
|View full text |Cite
|
Sign up to set email alerts
|

Early failure modalities in hip resurfacing

Abstract: Between 1996 and 2002, we treated 60 patients (65 hips) by hip resurfacing. The notes and radiographs of these cases were studied retrospectively and the modalities of failure identified. At a mean follow-up of 51 months, 14 of these cases (22%) required revision surgery. One patient had died from unrelated causes and one was lost to follow-up. At the time of primary surgery, the mean age of the patients in our series was 55 years. The commonest mechanism of failure in our series was fractured neck of femur (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…With regard to return to sport after joint replacement, Wilde et al found no signifi cant differences in the rate of return to sport according to the type of implanted prosthesis [ 80 ] . Cutts et al [ 81 ] found 14 revisions (22%) in a series of 65 hips (Corin-HAP) with a mean follow-up of 51 months and a mean age of 55 years. There were femoral neck fractures in six hips (four women over 60 years) with a mean occurrence at 23 weeks, cup loosening in four hips, increased avascular necrosis in one hip, pain in two hips, and infection in one hip.…”
Section: Current Resurfacing Prosthesesmentioning
confidence: 98%
“…With regard to return to sport after joint replacement, Wilde et al found no signifi cant differences in the rate of return to sport according to the type of implanted prosthesis [ 80 ] . Cutts et al [ 81 ] found 14 revisions (22%) in a series of 65 hips (Corin-HAP) with a mean follow-up of 51 months and a mean age of 55 years. There were femoral neck fractures in six hips (four women over 60 years) with a mean occurrence at 23 weeks, cup loosening in four hips, increased avascular necrosis in one hip, pain in two hips, and infection in one hip.…”
Section: Current Resurfacing Prosthesesmentioning
confidence: 98%